Generating Competitive Advantages in the NBA using Data Analytics - Berger, T.; Daumann, F.; Kuchinke, B. A. (Sportinformatik XII. 12. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie" vom 5.-7. September 2018 in Garching. Abstracts., 2018)
Professional sports - as a highly competitive field - has recognized the data analytics trend and seems to invest more and more money, time and faith in it. In the pursuit of sustainable financial and on-field success, many ambitious and forward-thinking sports organizations, leagues and teams are implementing data analytics in their management processes to gain potential benefits.This paper is taking first steps in researching the issue of data analytics application in sports with a special focus on the franchises of the National Basketball Association. "Competing on analytics" has become a serious path to success for many NBA teams. Still, the question remains: what kind of impact does this development have? Can the franchises use data analytics as an organizational resource to gain a competitive advantage over their opponents? If so, in what areas can they apply data analytics and can we measure potential benefits that result from implementing this approach into the management process? This paper is looking for answers to these questions. The theoretical part provides a framework regarding how data analytics should be viewed in the sports context. After defining it as a structured process with four steps and proving that it can be a source of competitive advantage, concrete areas of application for analytics in sports and especially in basketball will be discussed. Deriving from the Sports Policy Analytics Functional Relationships Model it can be shown that data analytics could be of use for NBA franchises to improve their management choices in talent acquisition, maximizing the on-field output of their athletes and lower their player salary costs.